The proselyte and the prophet : character development in Targum Ruth - Brady, Christian M. M. (Supplement to Aramaic Studies, 2016)
The Proselyte and the Prophet: Character Development in Targum Ruth by Christian M. M. Brady is an exegetical study of Targum Ruth with a focus upon the transformation of the biblical characters into exemplars of rabbinic piety. Ruth becomes the ideal proselyte while Boaz is presented as a judge, a scholar of the Law, and a prophet. Brady demonstrates that the Targumist follows standard Targumic practice, rendering each Hebrew word of the biblical text into Aramaic, while making additions that further his agenda of presenting Ruth as a rabbinic model to be emulated. In addition to the character analysis Brady provides a transcription of the manuscript Valmadonna 1, a new translation into English, and a verse-by-verse commentary of Targum Ruth.